Characterization of Noradrenaline-Induced Increases in Intracellular Ca2+ Levels in Chinese Hamster Ovary Cells Stably Expressing Human α1A-Adrenoceptor - Takahiro Horinouchi; Yumie Miyake; Tadashi Nishiya; Arata Nishimoto; Shoko Yorozu; Atsushi Jinno; Emi Kajita; Soichi Miwa (Elsevier, 2007)
The mechanism for noradrenaline (NA)-induced increases in intracellular Ca2+, concentration ([Ca2+]i) and physiological significance of Na+ influx through receptor-operated channels (ROCs) and store-operated channels (SOCs) were studied in Chinese hamster ovary (CHO) cells stably expressing human α1A-adrenoceptor (α1A-AR). [Ca2+]i was measured using the Ca2+ indicator fura-2. NA (1 µM) elicited transient and subsequent sustained [Ca2+]i increases, which were inhibited by YM-254890 (Gαq/11 inhibitor), U-73122 (phospholipase C (PLC) inhibitor), and bisindolylmaleimide I (protein kinase C (PKC) inhibitor), suggesting their dependence on Gαq/11/PLC/PKC. Both phases were suppressed by extracellular Ca2+ removal, SK&F 96365 (inhibitor of SOC and nonselective cation channel type-2 (NSCC-2)), LOE 908 (inhibitor of NSCC-1 and NSCC-2), and La3+ (inhibitor of transient receptor potential canonical (TRPC) channel). Reduction of extracellular Na+ and pretreatment with KB-R7943, a Na+/Ca2+exchanger (NCX) inhibitor, inhibited both phases of [Ca2+]i increases. These results suggest that 1) stimulation of α1A-AR with NA elicits the transient and sustained increases in [Ca2+]i mediated through NSCC-2 that belongs to a TRPC family; 2) Na+ influx through these channels drives NCX in the reverse mode, causing Ca2+ influx in exchange for Na+ efflux; and 3) the Gαq/11/PLC/PKC-dependent pathway plays an important role in the increases in [Ca2+]i. Keywords:: α1A-adrenoceptor, store-operated channel, nonselective cation channel, Na+/Ca2+ exchanger, intracellular free Ca2+ concentration